2003
DOI: 10.1002/cncr.11587
|View full text |Cite
|
Sign up to set email alerts
|

Detection of UGT1A10 polymorphisms and their association with orolaryngeal carcinoma risk

Abstract: BACKGROUND UGT1A10 exhibits glucuronidating activity against metabolites of the tobacco smoke carcinogen, benzo(a)pyrene, and is expressed highly in numerous target tissues for tobacco‐related cancers including the upper aerodigestive tract. The current study was conducted to determine the prevalence of genetic polymorphisms in the UGT1A10‐specific region of the UDP‐glucuronosyltransferase family 1A locus and their relationship with risk for orolaryngeal carcinoma. METHODS The authors analyzed UGT1A10‐specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 25 publications
0
58
0
Order By: Relevance
“…For the identification of UGT1A9 polymorphisms and determination of prevalence in different racial groups, our population included 253 whites, 164 African Americans, and 59 Asians as described previously (Richie et al, 1997;Park et al, 2000;Elahi et al, 2003). The allele and genotype frequencies for polymorphisms in the CYP1A1, CYP2E1, GSTM1, GSTT1, and GSTP1 genes in this population were similar to those observed in a pooled analysis of more than 15,000 subjects who served as controls in other case-control studies (Garte et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…For the identification of UGT1A9 polymorphisms and determination of prevalence in different racial groups, our population included 253 whites, 164 African Americans, and 59 Asians as described previously (Richie et al, 1997;Park et al, 2000;Elahi et al, 2003). The allele and genotype frequencies for polymorphisms in the CYP1A1, CYP2E1, GSTM1, GSTT1, and GSTP1 genes in this population were similar to those observed in a pooled analysis of more than 15,000 subjects who served as controls in other case-control studies (Garte et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The variant T202I exhibited decreased activity in this system, whereas the M59I change did not result in significant activity change. The only other study focusing on UGT1A10 polymorphisms has examined its role in orolaryngeal carcinoma risk (Elahi et al, 2003). Elahi et al reported six UGT1A10 polymorphisms (including three non-synonymous SNPs) in three racial groups.…”
Section: Ugt1a10mentioning
confidence: 99%
“…The frequency of both the E139K and L244I amino-acid changes was significantly higher in African Americans compared with Caucasians, and these mutations were absent in Asians. The role of these polymorphisms in orolaryngeal cancer risk was evaluated in 115 African Americans and 115 matched controls (Elahi et al, 2003). Individuals with the 139E allele were found to have a significantly lower risk for orolaryngeal carcinoma, whereas no association was found between cancer and the L244I variant.…”
Section: Ugt1a10mentioning
confidence: 99%
“…The tests for assessing buccal cell changes associated with smoking included procedures that employed PCR (n = 10 articles; refs. 25,26,30,32,35,36,40,41,45,47) and DNA adduct technology (n = 9; refs. 38, 39, 46, 48, 49, 54, 57-59; Table 1).…”
Section: Gudakhu Yesmentioning
confidence: 99%